2003
DOI: 10.1046/j.1439-0418.2003.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of cotton plants expressing two toxin proteins from Bacillus thuringiensis: relative toxin contribution, toxin interaction, and resistance management

Abstract: Laboratory studies were performed to characterize the lepidopteran toxicity of cotton plants expressing two different toxin proteins from Bacillus thuringiensis (Bt), in order to assess insect resistance management implications of a commercial, two‐toxin transgenic cotton. An independent and additive interactive effect of two Bt δ‐endotoxins expressed by the transgenic cotton variety 15985 was demonstrated by examining the responses of Heliothis virescens (F.), Helicoverpa zea (Boddie), and Spodoptera frugiper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
1
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 42 publications
0
61
1
5
Order By: Relevance
“…However, unlike our results showing similar seasonal declines of about threefold in Cry1Ac and Cry2Ab in DP 164 B2RF, previous studies with other cultivars found that the seasonal decline in toxin concentration was generally less for Cry2Ab (35)(36)(37) than Cry1Ac (38)(39)(40)(41)(42). In any case, seasonal declines in the concentration of Bt toxins could be an important factor affecting redundant killing because there is extensive variation among cotton cultivars in patterns of production of Bt toxins (43).…”
Section: Discussioncontrasting
confidence: 98%
“…However, unlike our results showing similar seasonal declines of about threefold in Cry1Ac and Cry2Ab in DP 164 B2RF, previous studies with other cultivars found that the seasonal decline in toxin concentration was generally less for Cry2Ab (35)(36)(37) than Cry1Ac (38)(39)(40)(41)(42). In any case, seasonal declines in the concentration of Bt toxins could be an important factor affecting redundant killing because there is extensive variation among cotton cultivars in patterns of production of Bt toxins (43).…”
Section: Discussioncontrasting
confidence: 98%
“…Treatments Bt7 and Bt8 were considered repellants for H. armigera, suggesting that the physical and chemical factors act in different ways among cultivars and these factors are fundamentally important for the behavioral analysis of insects [36].…”
Section: Discussionmentioning
confidence: 99%
“…In Bollgard II, these proteins, Cry1Ac and Cry2Ab, are encoded by genes originating from the common soil bacterium Bacillus thuringiensis (Bt). These Cry proteins are both highly effective in killing certain lepidopteran larvae (caterpillars) [23]. Once ingested, the Cry proteins bind to specific molecular receptors on the lining of the caterpillar's gut, create holes in the gut, and quickly cause death [57].…”
Section: Commercialization Of Bollgard II In Burkina Fasomentioning
confidence: 99%